1. The problem statement, all variables and given/known data (1-cosx)/(1+cosx) = (cscx-cotx)^2 2. Relevant equations cscx = 1/sinx, cotx = cosx/sinx, sin^2x + cos^2x = 1 3. The attempt at a solution I have tried many different attempts, but I can't seem to make one side like the other. I took the (cscx-cotx)^2 and expanded it to csc^2x - 2cotxcscx+cot^2x = (1-2cosx+cos^2x)/sin^2x. Alternatively, (1-2cosx+cos^2x)/1-cos^2x I've done every rearrangement I can think of, but I can't figure how to pull one side out of the other. Any help is much appreciated.